2021
DOI: 10.1089/lrb.2020.0063
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy in the Time of COVID-19: Effect of Molybdenum-99 Shortage on Feasibility of Sentinel Node Mapping

Abstract: Background: In the current study, we reported our experience on sentinel node mapping of breast cancer patients during the extreme shortage of Mo99-Tc99m generators using Tc-99m phytate. Methods and Results: During the period from March 7, 2019, to April 18, 2020, due to disruption of molybdenum supply chain, we used low specific activity Tc-99m pertechnetate elute (0.5-2 mCi of 99m TcO 4 in 5 mL) for each kit preparation. Two or three intradermal periareolar injections were done for each patient (0.02-0.1 mCi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… 33 In Iran, Sadri et al reported on the successful application of low specific activity of Tc-99m elutes to help with diagnosis and treatment approaches, including surgery with generator shortages. 88 There was also a 35.5% reduction in breast cancer surgeries in Pakistan during the early stages of the pandemic. 89 Breast cancer patients were typically divided in Pakistan into those that require urgent surgery, those where surgery can be altered or delayed for 4–8 weeks, and those where surgery can be postponed until the end of the pandemic combined with other management approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 In Iran, Sadri et al reported on the successful application of low specific activity of Tc-99m elutes to help with diagnosis and treatment approaches, including surgery with generator shortages. 88 There was also a 35.5% reduction in breast cancer surgeries in Pakistan during the early stages of the pandemic. 89 Breast cancer patients were typically divided in Pakistan into those that require urgent surgery, those where surgery can be altered or delayed for 4–8 weeks, and those where surgery can be postponed until the end of the pandemic combined with other management approaches.…”
Section: Resultsmentioning
confidence: 99%
“… Surgeries of early breast cancer were significantly altered due to COVID-19, especially in Hubei. Sadri et al, Iran 88 Observational study 7 Mar 2019–18 Apr 2020 35 (48 years) Application of Tc-99m elute during Mo99-Tc-99m generator shortage SLNB can be done with excellent results using Tc-99m pertechnetate elute during Mo99-Tc-99m generator shortage. Using special personal protection, nuclear medicine Departments can perform lymphatic mapping and biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…Tc-99m can be produced through various nuclear transmutation methods, but commercially speaking, it is generally derived from molybdenum-99 ( 99 Mo, t h) via 235 U targets [ 1 ]. However, the current commercial production and distribution of 99m Tc rely on a complex supply chain that has proven itself prone to disruptions in years past, which was most recently observed during the SARS-CoV-2 pandemic [ 2 ]. Ultimately, this leads to delays in the diagnoses of patients due to postponed imaging procedures as well as the loss of material and capital.…”
Section: Introductionmentioning
confidence: 99%
“…The supply chain has been interrupted several times in recent years leading to shortages of the drug(s) [6][7][8][9]. Over the last decade, efforts to integrate redundancy within the production side of the supply chain (coordinated scheduling, back-up producers, varying production loads, etc.)…”
Section: Introductionmentioning
confidence: 99%